Fulminant Giant Cell Myocarditis and Cardiogenic Shock: An Unusual Presentation of Malignant Thymoma. (4th May 2010) - Koul, Deepak; Kanwar, Manreet; Jefic, Dane; Kolluru, Anuradha; Singh, Tejwant; Dhar, Sunil; Kumar, Preetham; Cohen, Gerald
Abstract : Malignant thymoma is rarely associated with giant cell myocarditis. We present a case study that illustrates this association and cardiogenic shock with underlying tamponade. The dramatic presentation of this scenario has not been previously described.